Post-imaging colorectal cancer or interval cancer rates after CT colonography: a systematic review and meta-analysis - Obaro, AE; Plumb, AA; Fanshawe, TR; Torres, US; Baldwin-Cleland, R; Taylor, SA; Halligan, S; Burling, DN (Elsevier, 2018)
Background CT colonography is highly sensitive for colorectal cancer, but interval or post-imaging colorectal cancer rates (diagnosis of cancer after initial negative CT colonography) are unknown, as are their underlying causes. We did a systematic review and meta-analysis of post-CT colonography and post-imaging colorectal cancer rates and causes to address this gap in understanding. Methods We systematically searched MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials. We included randomised, cohort, cross-sectional, or case-control studies published between Jan 1, 1994, and Feb 28, 2017, using CT colonography done according to international consensus standards with the aim of detecting cancer or polyps, and reporting post-imaging colorectal cancer rates or sufficient data to allow their calculation. We excluded studies in which all CT colonographies were done because of incomplete colonoscopy or if CT colonography was done with knowledge of colonoscopy findings. We contacted authors of component studies for additional data where necessary for retrospective CT colonography image review and causes for each post-imaging colorectal cancer. Two independent reviewers extracted data from the study reports. Our primary outcome was prevalence of post-imaging colorectal cancer 36 months after CT colonography. We used random-effects meta-analysis to estimate pooled post-imaging colorectal cancer rates, expressed using the total number of cancers and total number of CT colonographies as denominators, and per 1000 person-years. This study is registered with PROSPERO, number CRD42016042437. Findings 2977 articles were screened and 12 studies were eligible for analysis. These studies reported data for 19 867 patients (aged 18–96 years; of 11 590 with sex data available, 6532 [56%] were female) between March, 2002, and May, 2015. At a mean of 34 months' follow-up (range 3–128·4 months), CT colonography detected 643 colorectal cancers. 29 post-imaging colorectal cancers were subsequently diagnosed. The pooled post-imaging colorectal cancer rate was 4·42 (95% CI 3·03–6·42) per 100 cancers detected, corresponding to 1·61 (1·11–2·33) post-imaging colorectal cancers per 1000 CT colonographies or 0·64 (0·44–0·92) post-imaging colorectal cancers per 1000 person-years. Heterogeneity was low (I2=0%). 17 (61%) of 28 post-imaging colorectal cancers were attributable to perceptual error and were visible in retrospect. Interpretation CT colonography does not lead to an excess of post-test cancers relative to colonoscopy within 3–5 years, and the low 5-year post-imaging colorectal cancer rate confirms that the recommended screening interval of 5 years is safe. Since most post-imaging colorectal cancers arise from perceptual errors, radiologist training and quality assurance could help to reduce post-imaging colorectal cancer rates.